Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Section 5.8 - Solving Equations by Factoring and Problem Solving - Exercise Set: 34

Answer

{-7, 1}

Work Step by Step

1. Factor the equation. $x^{2}$ + 6x - 7 = 0 (x + 7)(x - 1) = 0 2. Apply the zero factor principle. a) x + 7 = 0 b) x - 1 = 0 3. Solve each equation. a) x = -7 b) x = 1 The solutions are {-7, 1}.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.